PRODUCTIVITY OF PEPPERMINT RHIZOMES AMONG DIFFERENT VARIETIES IN CONDITION OF FERTILIZER AND LIME APPLICATION - A.I. Morozov (Овощи России)
The results presented in the article concerns the variety productivity of annual and biennial peppermint rhizomes grown on sod-podzolic soils with successive and simultaneous addition of mineral, organic fertilizers and lime.